Pseudocryptand-type complexes of heterocyclic derivatives of bis(meta-phenylene)-32-crown-10 with diquat. Issue 1 (6th January 2016) - Niu, Zhenbin; Price, Terry L.; Slebodnick, Carla; Gibson, Harry W.
Graphical abstract: Abstract: The readily prepared dipicolinate, diquinaldate, and dinaphthyridate ester derivatives1c –1e of bis( m -phenylene)-32-crown-10 (BMP32C10) diol1b demonstrated improved association constants with diquat (3 ) compared with BMP32C10 itself (1a ). Importantly, the association constant of dinaphthyridyl BMP32C10 (1e ) with diquat is even higher than some BMP32C10-based cryptands, which are synthetically difficult to obtain. An unusual pseudocryptand-type alternating poly[2]pseudorotaxane was formed between1e and diquat in the solid state.